Identifying the effect of persuasion - Sung Jae Jun; Sokbae Lee (Centre for Microdata Methods and Practice (cemmap), 2019)
We set up an econometric model of persuasion and study identification of key parameters under various scenarios of data availability. We find that a commonly used measure of persuasion does not estimate the persuasion rate of any population in general. We provide formal identification results, recommend several new parameters to estimate, and discuss their interpretation. Further, we propose methods for carrying out inference. We revisit the empirical literature on persuasion to show that the persuasive effect is highly heterogeneous. We also show that the existence of a continuous instrument opens up the possibility of point identification for the policy-relevant population.
Keywords: C21; D72; L82; 330; Communication; Media; Persuasion; Partial Identification; Treatment Effects